Of Trojan Horses and Terrorist Representations: Mom Bombs, Cross-Dressing Terrorists, and Queer Orientalisms - Magnet, S.; Mason, C.L. (Université d'Ottawa | University of Ottawa, 2014)
ABSTRACT This article employs anti-racist feminist theory to respond to a document published by the Department of Homeland Security United States in 2008. This document communicated the threatening possibility that women would use burqas or pregnancy prosthetics to hide bombs. Focusing on this report, the authors explore how the bodies of Muslim women have become spectacular in the post-9/11 period. Working at the intersections of gender, modernity, and visibility, they demonstrate that representations of Muslim women as threats is a new Orientalist discourse that justifies aggressive interventions against Muslim women, including new technologies such as backscatter X-rays. RÉSUMÉ Cet article s'appuie sur la théorie féministe antiraciste pour répondre à un document publié par le département de la sécurité intérieure des États-Unis en 2008. Le document avait comme but d'avertir le public de la possibilité que certaines femmes utiliseraient les burqas ou les prothèses de grossesse pour cacher des bombes. À partir de ce document, nous explorons la façon dont les corps des femmes musulmanes sont devenus spectaculaires dans les discours après g/11. En visant la relation entre le genre, la modernité, et la visibilité, nous démontrons que les représentations des corps des femmes musulmanes constituent un nouveau discours orientaliste qui vient justifier les interventions agressives contre les femmes musulmanes, telles les technologies de rétrodiffusion de rayons.